Technological Approaches and Quality Assessment of Mini-Tablets: A Review - Vetrivel R; Saraswathi T.S; N. Damodharan (The Bioscan, 2025)
The mini-tablets are a new solid oral dosage form, which is supposed to fulfill the emerging requirements of personalized drugs, particularly in the pediatric and geriatric patient groups. Mini-tablets can be characterized as a smooth tablet with a diameter of up to 3 mm; thus, it presents various benefits, such as excellent swallowability, flexibility in the dosing range, and excellent patient adherence. They may be manufactured to conventional processes, direct compression, dry and wet granulation with adaptations to suit their small size and low dose content. Mini- tablets may be prepared as immediate, sustained or pulsatile release systems, or formulated as biphasic release systems. They can also be coated to mask bitter tastes or deliver drugs specifically to various locations. They are used also in bioadhesive systems and floating and orally disintegrating formulations. Improved 3D printing and smart dispensing technologies also allow patient-specific dosing, digital health platform cross-over, and increased therapeutic success. The technological advancement of packaging like a stick pack, blister pack, capsule filling aids in maintaining a hygienic and precise dispensing. Nevertheless, issues like low drug payload, excellent production tolerance, and new, complicated packaging specifications shall have to be resolved. Nevertheless, despite these challenges, mini-tablets are a potentially valuable platform to deliver an individualized, safe, and efficient drug, a very positive step in the sphere of modern pharmaceutics.